The SMC-like RecN protein is at the crossroads of several genotoxic stress responses in Escherichia coli - Camus, Adrien; Espinosa, Elena; Zapater Baras, Pénélope; Singh, Parul; Quenech’Du, Nicole; Vickridge, Elise; Modesti, Mauro; Barre, François Xavier; Espéli, Olivier (Frontiers in Microbiology, 2023)
DNA damage repair (DDR) is an essential process for living organisms and contributes to genome maintenance and evolution. DDR involves different pathways including Homologous recombination (HR), Nucleotide Excision Repair (NER) and Base excision repair (BER) for example. The activity of each pathway is revealed in particular contexts, but the repair of most DNA lesions depends on their concomitant or subsequent action. In the present study, we used two genotoxic antibiotics, mitomycin C (MMC) and Bleomycin (BLM), to decipher the interplays between these different pathways in E. coli. We demonstrate that only a small set of DDR proteins are common to the repair of the lesions induced by these two drugs. Among them, RecN, an SMC-like protein, plays an important role by controlling sister chromatids dynamics and genome morphology at different steps of the repair processes. We further demonstrate that RecN influence on sister chromatids dynamics is not equivalent during the processing of the lesions induced by the two drugs. We observed that RecN activity and stability requires a pre-processing of the MMC-induced lesions by the NER but not for BLM-induced lesions. Those results show that RecN plays a major role in rescuing toxic intermediates generated by the BER pathway in addition to its well-known importance to the repair of double strand breaks by HR.